Immediate Legal Changes in Czechoslovak Education after WWII - Tereza Kolumber (Journal on European History of Law)
The text comprehensively analyses the immediate legal and structural changes in the Czechoslovak education system following WWII. It details the significant destruction caused by the Nazi occupation, which sought to eradicate Czech intelligentsia and limit educational opportunities. Postwar efforts were focused on rebuilding the educational infrastructure, reopening schools, repairing facilities, and re-establishing democratic values and pedagogical principles. The study employs a methodological approach examining legal documents, such as presidential decrees and government regulations, and contemporary sources like reports. It highlights initiatives to ensure equal access to education for all students, regardless of nationality or social status, and discusses the political and social factors that influenced the educational revival. The paper examines explicitly the historical regions of Bohemia, Moravia, and Silesia from May to December 1945, briefly mentioning the situation in Slovakia.